2017
DOI: 10.1080/14767058.2017.1383379
|View full text |Cite
|
Sign up to set email alerts
|

Propofol and fentanyl sedation for laser treatment of retinopathy of prematurity to avoid intubation

Abstract: The good level of anesthesia and analgesia achieved sustains the efficacy of sedation with propofol during laser photocoagulation to avoid intubation and mechanical ventilation during and after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Propofol, however, has been widely used as well during intubation and other procedures for sedation and anaesthesia 34–36. Thereby, the level of sedation achieved by the use of propofol was considered satisfactory during surgery in the study of Piersigilli et al , but this was not evaluated objectively 35…”
Section: Discussionmentioning
confidence: 99%
“…Propofol, however, has been widely used as well during intubation and other procedures for sedation and anaesthesia 34–36. Thereby, the level of sedation achieved by the use of propofol was considered satisfactory during surgery in the study of Piersigilli et al , but this was not evaluated objectively 35…”
Section: Discussionmentioning
confidence: 99%
“…Piersigili et al [12] demonstrated that fentanyl analgesia and propofol sedation were effective in this short-term surgery and had no side effects, thus forming the basis of a randomized trial to evaluate propofol safety. They stated that their aim was to avoid intubation in the neonatal patient group, but they used a laryngeal mask for airway safety.…”
Section: Discussionmentioning
confidence: 98%
“…6 While general anesthesia with intubation may be superior to intravenous sedation in providing ideal operating conditions, it does introduce risk associated with intubation and ventilation of premature infants previously stabilized on non-invasive ventilation strategies. Laryngeal mask airway use has been described with variable success 7 To minimize the risk of a poor retinal outcome, treatment should be performed as soon as possible. 1 Staffing issues however can create a scenario where the only option is to provide laser therapy out of normal working hours.…”
Section: Backg Round and S I G Nific An Cementioning
confidence: 99%
“…While general anesthesia with intubation may be superior to intravenous sedation in providing ideal operating conditions, it does introduce risk associated with intubation and ventilation of premature infants previously stabilized on non‐invasive ventilation strategies. Laryngeal mask airway use has been described with variable success 7 Alternative approaches based on opiate sedation and avoidance of volatile anesthetics have been promoted by units where the availability of ophthalmologists, operating theater sessions, and pediatric anesthetists is limited. Other concerns include avoidance of repeated anesthetic exposure as they may affect neurodevelopment 8 …”
Section: Background and Significancementioning
confidence: 99%